A Justified Plan Graph (JPG) grammar approach to identifying spatial design patterns in an architectural style. Issue 1 (January 2018) - Lee, Ju Hyun; Ostwald, Michael J; Gu, Ning
This paper presents a hybrid approach that selectively merges aspects of both the theories of Shape Grammar and Space Syntax to investigate spatial design patterns. The paper describes the development of a generic Justified Plan Graph (g-JPG) grammar. This grammatically nuanced, syntactically derived approach is then demonstrated through a more specific JPG (s-JPG) grammar to identify spatial design patterns in the rural domestic architecture of Glenn Murcutt. The results are then discussed in terms of Murcutt's architecture from four perspectives: grammatical transformation of syntax, epistemological questions, similarity or disparity and finally in terms of JPG variations. The findings of this paper suggest that the combined analytic approach facilitates the exploration of both the grammatical and syntactical genotypes of sets of architectural designs.